Animal Nutrition Research for Strengthening Animal Production and Health - Verma, Ashok; Singh, Putan (Indian Farming, 2015)
In the changing scenario of livestock production in the country, Animal Nutritionists are working on newer approaches to maximize the production potential of animals with nutritional interventions, nanotechnology based feed supplements, strategic supplementation of plants containing secondary metabolites and clinical nutrition. These are some of the areas which need special attention of researchers to get maximum output with the feed resources available with the farmers.